2021
DOI: 10.1177/25168657211008108
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation at Birth is Associated with Childhood Serum Immunoglobulin E Levels

Abstract: Immunoglobulin E (IgE) is known to play an important role in allergic diseases. Epigenetic traits acquired due to modification of deoxyribonucleic acid (DNA) methylation (DNAm) in early life may have phenotypic consequences through their role in transcriptional regulation with relevance to the developmental origins of diseases including allergy. However, epigenome-scale studies on the longitudinal association of cord blood DNAm with IgE over time are lacking. Our study aimed to examine the association of DNAm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…26 Exposure to arsenic during pregnancy has been associated with a DNA methylation pattern in infants 27 as well as changes in children's immunoglobulin E levels. 28 Although metals other than arsenic (ie, cadmium, lead, cobalt, copper, nickel, thallium, and zinc)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Exposure to arsenic during pregnancy has been associated with a DNA methylation pattern in infants 27 as well as changes in children's immunoglobulin E levels. 28 Although metals other than arsenic (ie, cadmium, lead, cobalt, copper, nickel, thallium, and zinc)…”
Section: Discussionmentioning
confidence: 99%
“… 26 Exposure to arsenic during pregnancy has been associated with a DNA methylation pattern in infants 27 as well as changes in children’s immunoglobulin E levels. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Environmental and epigenetic factors like DNA methylation, histone modification and microRNA’s can alter the expression of these genes. Studies regarding DNA methylation changes in cytokine genes such as interferon gamma (IFN-γ), interleukin-4 (IL-4) and IL-5 and in Forkhead box P3 (FoxP3) indicate that changes in DNA methylation may predispose IgE-mediated food sensitization or allergy in early childhood ( 35 38 ). Acevedo et al studied the DNA methylation levels in mononuclear leukocytes from mothers and their children.…”
Section: Immunological Changes In Early Solid Food Introduction In Th...mentioning
confidence: 99%
“…However, the predictive capabilities in prospective associations with aeroallergen sensitization were limited, indicating that DNAm might be a result rather than a predictor of allergic sensitization. On the other hand, studies investigating DNAm in cord-blood found associations with higher IgE levels later in life [ 8 , 9 ], indicating a certain predictive potential.…”
Section: Introductionmentioning
confidence: 99%